Crohn's disease with dilated cardiomyopathy in a child: An experience with heart transplantation. (28th April 2021) - Konduri, Anusha; Blake, Jennifer; Aggarwal, Sanjeev
Abstract: Background: DCM has rarely been reported in children with CD, but is a recognized complication in adults. DCM with uncontrolled heart failure may need heart transplantation, which could be challenging in CD. Case Description: We present a 9‐year‐old female with CD who was diagnosed with DCM and a measured Ejection fraction ~25.8%. She was initiated on heart failure treatment, but continued to have progressive symptoms and underwent bicaval OHT three months after her initial presentation. Her post‐operative course was complicated by perforation of the rectosigmoid junction requiring exploratory laparotomy and primary repair of the perforation. This was believed to be secondary to her underlying CD and possibly reperfusion injury after heart transplant. During the first‐year post heart transplant, she had 4 episodes of acute cellular rejection. These episodes were treated with high dose steroids with good results. The patient has been in remission from CD since transplantation. For the last two years she is doing well, with no further rejection episodes on current immunosuppression. Conclusion: DCM, though rare, can occur in patients with CD, whether active or in remission. The development of DCM could be insidious and keeping a high index of suspicion is important and subtle signs suggestive of cardiac involvement should warrant further investigation. The post‐transplant management can be challenging with early morbidity in the first post‐transplant year but overall good median survival and quality of life for our patient to date.